The Integration of Optical Stimulation in a Mechanically Dynamic Cell Culture Substrate - Imboden, Matthias; Chen, Sophia; Gudozhnik, Olexandr; Pollock, Corey; Javor, Josh; Bishop, David; Shea, Herbert; Rosset, Samuel (Frontiers in Bioengineering and Biotechnology, 2022)
Presented is a cell culture well with integrated mechanical and optical stimulation. This is achieved by combining dielectric elastomer soft actuators, also known as artificial muscles, and a varifocal micro-electromechanical mirror that couples light from an optical fibre and focuses it onto the transparent cell substrate. The device enables unprecedented control of in-vitro cell cultures by allowing the experimenter to tune and synchronise mechanical and optical stimuli, thereby enabling new experimental assays in optogenetics, fluorescent microscopy, or laser stimulation that include dynamic mechanical strain as a controlled input parameter.